Changes in agrarian structure, capital, and access (case study of land redistribution program in Pasawahan Village, Ciamis District) - Galih Andreanto; Endriatmo Soetarto; Rina Mardiana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The agrarian structure is a changing place where people fight for certain positions. This study looks at how the agrarian structure changed before, during, and five years after the land redistribution program was put into place in Pasawahan Village, Ciamis, West Java. For this research, both quantitative and qualitative descriptive case studies are used. Respondents whose information was used came from a group of 540 land redistribution recipients who owned a total of 838 plots of land. The results showed that there was a big difference between the agrarian structure before land redistribution, at the time land redistribution was put into place, and after it was put into place. When land redistribution is put into place, economic and symbolic capital, access to jobs, and access to knowledge have a negative effect on the agrarian structure. At the same time, capital makes the agrarian structure better. Access to knowledge has a bad effect on the agrarian structure, while redistribution of land, economic and symbolic capital, and access to technology all have a positive effect. After the land is redistributed, capital has a positive effect on the agrarian structure.